No doing without time. (2019) - Pan, Shen; Carruthers, Peter
Abstract: Hoerl & McCormack claim that animals don't represent time. Because this makes a mystery of established findings in comparative psychology, there had better be some important payoff. The main one they mention is that it explains a clash of intuition about the reality of time's passage. But any theory that recognizes the representational requirements of agency can do likewise.